Measuring the economy: problems and prospects - Keating, William (Statistical and Social Inquiry Society of Ireland, 2001)
This paper discusses the statistical measurement of economic growth and examines some issues arising in that context. It looks at the treatment of productivity and quality improvements, especially as regards non-market services. Measurement issues arising from globalisation are also identified and the impact of foreign direct investment enterprises on the main aggregates is examined. Finally, the wider question of economic well-being is discussed and examples are given of development work in this regard in other countries.
Read before the Society, 26 October 2000
Keywords: Economic growth; Measurement; Foreign Direct Investment; 314.15